Novel field cage design for the PandaX III double beta decay experiment. (23rd October 2017) - Chaiyabin, P.; Giboni, K.L.; Han, K.; Ji, X.; Juyal, P.; Kobdaj, C.; Liu, J.; Lomon, J.; Pasaja, N.; Poolcharuansin, P.; Rujirawat, S.; Songsiriritthigul, P.; et al.
Abstract: PandaX III is a High Pressure gaseous xenon Time Projection Chamber for Double Beta Decay detection. It will be installed deep underground in the JinPing Laboratory in Szechuan province, China. During its first phase the detector will operate with 200 kg of enriched^{136} 136 Xe. The detector consists of a mesh cathode in the center of a cylindrical vessel and Micro-Bulk Micro-Megas at both ends to read out the drifting charges. The active volume is surrounded by an array of electrodes to shape the homogeneous drift field, the so called field cage. Gaseous xenon, however, is a poor dielectric. It would require in excess of 10 cm to safely stand off the HV between these electrodes and the grounded detector walls. Nearly a quarter of our available xenon would be wasted in this dead space. In a new design the electric field outside the field shaping is totally contained in a cylinder 1.6 m diameter and 2 m long. For manufacturing two 50 mm thick Acrylic plates are bend into half cylinders and bonded together. The outside surface of the cylinder is covered with a copper mesh as ground plane. The gap between field cage and detector vessel can be now reduced to 1 mm, and this gap is field free. The amount of wasted xenon is reduced by a factor 100. The field shaping electrodes and the resistive divider network are mounted on 5 mm thick Acrylic panels suspended on the inside of the field cage. This design is realized with low radioactivity materials.